Statewide Mathematics Professional Development: Teacher Knowledge, Self-Efficacy, and Beliefs. (June 2016) - Carney, Michele B.; Brendefur, Jonathan L.; Thiede, Keith; Hughes, Gwyneth; Sutton, John
We examined the impact of a state-mandated K-12 mathematics professional development course on knowledge, self-efficacy, and beliefs of nearly 4, 000 teachers and administrators. Participants completed the Mathematical Thinking for Instruction course, emphasizing student thinking, problem-solving, and content knowledge specific to mathematics instruction. Inventories utilizing items from the Learning Mathematics for Teaching project measured changes in participants' Mathematical Knowledge for Teaching (MKT) and an end-of-course self-evaluation enabled analysis of changes self-efficacy and beliefs. Statistically significant changes were found in all three variables. This study adds to our understanding of the potential usefulness of mandating large-scale professional development as a policy vehicle for influencing educators' mathematics knowledge and beliefs.